AB0961 Clinical Utility of 18F-Fdg-Pet/Ct for Evaluation of Patients with Musculoskeletal Sarcoidosis. (10th June 2014) - Manali, E.; Pianou, N.; Georgakopoulos, A.; Papaioannou, A.; Roussou, A.; Papadaki, G.; Kolilekas, L.; Gialafos, E.; Tomos, J.; Kagouridis, K.; Chatziioannou, S.; Papiris, S.
Abstract : Background: Sarcoidosis is a systemic granulomatous disease of unknown cause mainly affecting the lung and the lymphatic system. Muscles, joints and bones may also be involved symptomatically or asymptomatically. Detection of active musculoskeletal sarcoidosis may have therapeutic and prognostic clinical implications. 18 F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography ( 18 F-FDG PET/CT) has improved the diagnostic accuracy of extrapulmonary sarcoidosis. Objectives: To highlight the clinical utility of 18 F-FDG-PET/CT for the evaluation-not yet established-of patients with musculoskeletal sarcoidosis. Methods: All biopsy proven sarcoidosis patients referred to our Pulmonary Medicine Department were evaluated. Epidemiological, clinical, laboratory and functional data were collected after informed consent. Patients further submitted to 18 F-FDG-PET/CT were included in the study. All patients fasted more than 18 hours and consumed low-carbohydrate meals the day before the PET/CT study for sufficient suppression of physiological myocardial glucose uptake. 18 F-FDG was injected intravenously (5.5 MBq/kgr) and none of the patients had blood glucose levels >180 mg/dl. PET/CT images were obtained initially in brain and then from the base of the head to the feet. Results: Twenty one patients, 66.7% female, mean age (±SD) of 46.5±12.6 years and stage 0, I, II, III, IV at rates of 4.7%, 46.1%, 23.8%, 9.5% and 9.5% respectively were studied. Disease duration was 39 (range 10-88) months. Mean FEV1, FVC and DLCO values were 94.5% ±14.5, 99.8% ±15.5 and 96.9% ±12 of predicted respectively. Five out of 21 patients (23.8%) revealed increased radiotracer uptake at the musculoskeletal system as follows: bone lesions (n=4), cutaneous lesions (n=2), subcutaneous lesions (n=2) and muscle lesions (n=2). Bone lesions involved the pelvis (3), sacrum (2), tibia (2), thoracic and lumbar vertebrae (1), femur (1) and the phalanges of the feet (1). No patient was symptomatic with pain. When patients with musculoskeletal disease were compared to those without, they were found significantly younger (50.1±12.8 vs 36.2±2.4 years, p=0.03). No significant differences were found as far as pulmonary function and 6 minute walk test parameters are concerned as well as biochemical indices such as creatine kinase, alkaline phosphatase or serum calcium between the two groups. Conclusions: 18 F-FDG PET/CT revealed occult musculoskeletal involvement in almost one quarter of sarcoidosis patients studied. No other clinical, functional or biochemical indices examined were suggestive of the musculoskeletal manifestation of the disease. References: Soussan M, et al. Functional imaging in extrapulmonary sarcoidosis: FDG-PET/CT and MR features.Clin Nucl Med 2014; 39: e146-59 Zisman DA, et al. Sarcoidosis involving the musculoskeletal systemSemin Respir Crit Care Med 2002; 23: 555-70 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5645